Transcriptome analysis reveals hypoxic response key genes and modules as well as adaptive mechanism of crucian carp (Carassius auratus) gill under hypoxic stress - Xing, Mengchao; Rong, Zhen; Zhao, Xin; Gao, Xiaowei; Hou, Zhiguang; Zhang, Lihan; Khor, Waiho; Xu, Yihuan; Chen, Li; Wu, Chengbin (Frontiers in Immunology, 2025)
Fish gill tissue is a primary organ responsive to acute oxygen deprivation or dissolved oxygen (DO) fluctuations in aquatic environments. However, the adaptive mechanism of crucian carp to hypoxic stress remains largely unknown. Here, we investigated gill physiological and transcriptomic changes of crucian carp exposed to hypoxic conditions (dissolved oxygen concentration of 0.6 ± 0.3 mg/L) for different durations (0 d, 1 d, 2d, 3d, 4 d, and 5d). Transcriptomic analysis revealed that the hypoxia group (0.6 ± 0.3 mg/L DO) exhibited a reduction in interlamellar cell mass (ILCM) on the gill filaments, compared with the control group (6.6 ± 0.3 mg/L DO). With prolonged hypoxia stress, the epithelial cells in the gill lamellae became sparse at 3 d to 5 d, and gill vacuoles were increased. A total of 3,502 differentially expressed genes (DEGs) were identified, and 3 hypoxia-specific modules were screened through differential expression analysis, weighted gene co-expression network analysis (WGCNA), and Bayesian network analysis. The apoptosis, necroptosis, efferocytosis and FoxO signaling pathways were significantly enriched based on the KEGG enrichment pathway analysis. The VEGF pathway genes are significantly expressed, enhancing the generation of microvessels in the gill filaments, and improving the capacity to carry oxygen, thus enabling the crucian carp to adapt to hypoxia stress. Hypoxia activated glycolysis, enhanced anaerobic metabolism, promoted β-oxidation of fatty acids, providing energy and maintaining normal physiological metabolism, eventually improving antioxidant and immune capabilities in crucian carp. In summary, this study reveals the molecular mechanism by which crucian carp adapt to hypoxic stress. Our findings provide valuable references for promoting the healthy aquaculture of hypoxic-sensitive fish and breeding hypoxia-tolerant fish varieties.